Barriers to utilisation of cervical cancer screening in Sub Sahara Africa: a systematic review - Lim, J.N.W.; Ojo, A.A. (European journal of cancer care, 2017)
Background Cervical cancer is the commonest cause of cancer‐related death in Sub Sahara Africa (SSA). Both primary and secondary preventive services are available but utilisation remain low. This systematic review aims to summarise reported barriers preventing women from utilising cervical cancer screening services in SSA. Method Electronic searches on MEDLINE, EMBASE, PsycINFO, BIOSIS preview, Global Health, PubMed, Cochrane library, CINAHL, ISI Web of Knowledge and Google scholar and quality assessment of the included studies were performed. A meta‐analysis was applied to identify major themes. Results Eight studies exploring reasons women did not utilise cervical cancer screening were included. Women in SSA reported similar barriers despite cultural and language diversity in the region. Women reported fear of screening procedure and negative outcome, low level of awareness of services, embarrassment and possible violation of privacy, lack of spousal support, societal stigmatisation, cost of accessing services and health service factors like proximity to facility, facility navigation, waiting time and health care personnel attitude. Conclusion Strategies for improving uptake and utilisation of cervical screening in SSA should focus on improving cervical health education, addressing cultural beliefs and practices and improving spousal support and empowering women, as well as addressing physical access problem, costs and improving staff attitude.